Chasing the Comet : a Scottish-Canadian Life. - Koretchuk, Patricia (Wilfrid Laurier University Press, 2006)
"Dour Scot" is the wrong description for David Caldow, who leads readers on a romp from the early twentieth century to the present, from an insular Scottish village to modern-day, multicultural British Columbia, from boyhood to old age. Throughout the tour he shares decades of laughter, tears, fears, and growth. In 1910, the certain path of David's life in Scotland is disrupted by the visit of an awe-inspiring comet. This brilliant visitor inspires the boy to dream of circling the world, like the comet, even though his life's goal is to become a farm manager, like his father. As a young man.